Ontology e-Learning Content berbasis Web Semantic - Bernard Renaldy Suteja; Ahmad Ashari (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2008)
E-Learning content being a barrier for ELearning is no longer true on today’s Internet. The currentconcerns are how to effectively annotate and organize available content (both textual and non-textual) tofacilitate effective sharing, reusability and customization. In this paper, we explain a component-orientedapproach to organize content in an ontology. We also illustrate our 3-Tier E-Learning Content ManagementArchitecture and relevant Interfaces. We use a simple yet intuitive example to successfully demonstrate thecurrent working prototype which is capable of compiling personalized course materials. The system e-Learningprototype uses the ontology.Keywords: e-Learning, Ontology, Semantic Web